Regional Mapping of Small‐Scale Equatorial Ionospheric Irregularities Using Swarm Echo Satellite Measurements - Ali Mohandesi; David J. Knudsen; Susan Skone; Richard B. Langley; Andrew W. Yau (Space Weather)
Abstract We propose a novel approach to produce regional maps of small‐scale scintillation‐causing irregularities using a single satellite. To construct the maps, we employ several ionospheric GPS indices, including total electron content, high‐resolution ROTI, and S4, calculated from the Swarm Echo GPS Attitude, Positioning, and Profiling Experiment Occultation (GAP‐O) receiver with its antenna pointed upward. GAP‐O's high‐sample‐rate observations enable irregularities as small as 320 m to be resolved. We present two case studies in which we compare the maps with in situ measurements of irregularities and simultaneous vertical TEC maps obtained from the ground. In situ measurements of net current onto the external surface of the Imaging and Rapid‐scanning Ion Mass Spectrometer sensor on board Swarm Echo were utilized to quantify plasma density fluctuations. Then, we apply the method to synthetic data to illustrate the efficacy of the method. Modeling results show that the irregularity maps can determine the horizontal geo‐locations of small‐scale irregularities, though with significant uncertainties in the cross‐track direction (east‐west). As Swarm Echo traverses different altitudes, these maps provide additional information on the altitudinal distribution of plasma fluctuations. This technique facilitates a better understanding of the morphology of scintillation‐causing irregularities, which are challenging to map from ground‐based receiver arrays alone.